2002
DOI: 10.1002/ajmg.10225
|View full text |Cite
|
Sign up to set email alerts
|

Pure 6p22‐pter trisomic patient: Refined FISH characterization and genotype‐phenotype correlation

Abstract: First described in 1971, partial trisomy 6p is uncommon and generally secondary to a familial reciprocal translocation. The proximal breakpoint of the reported cases varies from p11 to p25. We here report on a patient with moderate mental retardation, craniofacial and pigmentary anomalies, proteinuria, and hyperglycemia who was found to have a mosaic karyotype 46,X,add(Y)(q12)/45,X. Fluorescence in situ hybridization (FISH) enabled us to identify that the additional material on Yqh derived from 6p and to defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 13 publications
1
25
0
Order By: Relevance
“…''Pure'' trisomy of the terminus of 6p (i.e., trisomy of 6p without an associated structural abnormality of another chromosome) is extremely rare, and has been reported for just five cases [Chiyo et al, 1975;Phelan et al, 1986;Rothlisberger et al, 1999;Engelen et al, 2001], including one patient that was mosaic with a 45,X cell line [Giardino et al, 2002]. We were unable to find any reports of tetrasomy of 6p.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…''Pure'' trisomy of the terminus of 6p (i.e., trisomy of 6p without an associated structural abnormality of another chromosome) is extremely rare, and has been reported for just five cases [Chiyo et al, 1975;Phelan et al, 1986;Rothlisberger et al, 1999;Engelen et al, 2001], including one patient that was mosaic with a 45,X cell line [Giardino et al, 2002]. We were unable to find any reports of tetrasomy of 6p.…”
Section: Discussionmentioning
confidence: 80%
“…As reviewed by Giardino et al [2002], 31 of the reported trisomy 6p cases exhibit an associated deletion of chromosomal material due an unbalanced rearrangement of a parental translocation, 10 were de novo cases, and 1 [Delatycki et al, 1999] represented direct paternal inheritance. The breakpoints associated with the terminal rearrangements span from 6p11 to 6p25, and clinical findings do not appear to be dependent upon the amount of trisomic material [Scarbrough et al, 1986].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, when pictures are available and patients are comparable in terms of sex and age, a strong physiognomic correlation was noted in cases reported by Mégarbané et al [2002], Giardino et al [2002], Pierpont et al [2000], Delatycki et al [1999], and Ferrando et al [1981]. All of these cases shared the involvement of the distal tract of 6p25pter with a proximal breakpoint that varies from 6p21.3 to p.25.…”
Section: Discussionmentioning
confidence: 90%
“…Characteristic craniofacial findings include craniosynostosis, prominent forehead, blepharophimosis and blepharoptosis, hypotelorism, low-set or malformed ears, small pointed chin, short and bulbous nose with tiny nares, choanal atresia, prominent nasal bridge, and small mouth with thin lips. Intellectual disability, epilepsy, mental retardation, autism, brain abnormalities, hearing loss, ocular defects, or immunodeficiency with susceptibility to pulmonar infections have also been reported [Smith and Pettersen, 1985;Fryns et al, 1986;Burd et al, 1988;Krassikoff and Sekhon, 1989;Katafuchi et al, 1992;Wauters et al, 1993;Giardino et al, 2002;Bart et al, 2011]. Furthermore, this chromosome anomaly is associated with a reduced life span [Villa et al, 2000;Stohler et al, 2007].…”
mentioning
confidence: 99%